PENGEMBANGAN VIDEO TUTORIAL PRAKTIKUM LAPANGAN BIOLOGI SMA KELAS X - Pertiwi, Siti Rahayu; Linggasari, Mariani Natalina; Suzanti, Fitra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Practicum are required in biological learning to achieve learning goals. The implementation of practicum has several obstacles, one of which during the current pandemic cannot be implemented directly in schools. Therefore, innovation is needed in the learning media to support the implementation of practicums, namely video tutorials. This research aims to develop field practicum tutorial videos to make it easier for students conduct practicum independently. The research was conducted from April – October 2021. Video development tutorial practicum using the ADDIE model consisting of 5 stages, namely Analyze, Design, Development, Implementation, and Evaluation. However, this study was only done until the development stage. At the development stage, the data source is obtained from the validation sheet and response questionnaire. The result showed that the field practicum tutorial videos developed are of good quality and can be used as a learning medium. The validation results obtained an average score of 3,69 with a very valid category, the results of limited trials of phase I is 3,82 with very good categories, and the results of limited trials of phase II is 3,61 with very good categories.Key Words: Biology, Field Practicum, Video Tutorials